Assessment of Human Disc Degeneration and Proteoglycan Content Using T(1ρ)-weighted Magnetic Resonance Imaging - Johannessen, Wade (2006)
STUDY DESIGN: T(1ρ) relaxation was quantified and correlated with intervertebral disc degeneration and proteoglycan content in cadaveric human lumbar spine tissue. OBJECTIVE: To show the use of T(1ρ)-weighted magnetic resonance imaging (MRI) for the assessment of degeneration and proteoglycan content in the human intervertebral disc. SUMMARY OF BACKGROUND DATA: Loss of proteoglycan in the nucleus pulposus occurs during early degeneration. Conventional MRI techniques cannot detect these early changes in the extracellular matrix content of the disc. T(1ρ) MRI is sensitive to changes in proteoglycan content of articular cartilage and may, therefore, be sensitive to proteoglycan content in the intervertebral disc. METHODS: Intact human cadaveric lumbar spines were imaged on a clinical MR scanner. Average T(1ρ) in the nucleus pulposus was calculated from quantitative T(1ρ) maps. After MRI, the spines were dissected, and proteoglycan content of the nucleus pulposus was measured. Finally, the stage of degeneration was graded using conventional T(2) images. RESULTS: T(1ρ) decreased linearly with increasing degeneration (r=−0.76, P < 0.01) and age (r=−0.76, P < 0.01). Biochemical analysis revealed a strong linear correlation between T(1ρ) and sulfated-glycosaminoglycan content. T(1ρ) was moderately correlated with water content. CONCLUSIONS: Results from this study suggest that T(1ρ) may provide a tool for the diagnosis of early degenerative changes in the disc. T(1ρ)-weighted MRI is a noninvasive technique that may provide higher dynamic range than T(2) and does not require a high static field or exogenous contrast agents.